RNA-Binding Protein MSI2 Binds to miR-301a-3p and Facilitates Its Distribution in Mitochondria of Endothelial Cells - Guo, Qian Qian; Gao, Jing; Wang, Xiao Wei; Yin, Xian Lun; Zhang, Shu Cui; Li, Xue; Chi, Lian Li; Zhou, Xiao Ming; Wang, Zhe; Zhang, Qun Ye (Frontiers in Molecular Biosciences, 2021)
Numerous miRNAs have been detected in mitochondria, which play important roles in many physiological and pathophysiological processes. However, the dynamic changes of miRNA distribution in mitochondria and their mechanisms in reactive oxygen species (ROS)-induced endothelial injury remain unclear. Therefore, miRNA levels in whole cells and mitochondria of H2O2-treated endothelial cells were analyzed by small RNA sequencing in the present study. The results showed that H2O2 significantly reduced the relative mitochondrial distribution of dozens of miRNAs in human umbilical vein endothelial cells (HUVECs). Among the high-abundance miRNAs, miR-301a-3p has the most significant changes in the redistribution between cytosol and mitochondria confirmed by absolute quantitative polymerase chain reaction (qPCR). To unravel the mechanism of miR-301a-3p distribution in mitochondria, RNA pull-down followed by label-free quantitative proteomic analysis was performed, and RNA-binding protein Musashi RNA binding protein 2 (MSI2) was found to specifically bind to miR-301a-3p. Western blotting and immunofluorescence colocalization assay showed that MSI2 was located in mitochondria of various cell types. H2O2 significantly downregulated MSI2 expression in whole endothelial cells, promoted the distribution of MSI2 in cytosol and decreased its distribution in the mitochondria. Moreover, overexpression of MSI2 increased the mitochondrial distribution of miR-301a-3p, whereas inhibition of MSI2 decreased its distribution in mitochondria. Thus, MSI2 might be responsible for the distribution of miR-301a-3p between cytosol and mitochondria in endothelial cells. Our findings revealed for the first time that MSI2 was involved in the regulation of miRNA distribution in mitochondria and provided valuable insight into the mechanism of mitochondrial distribution of miRNAs.